“Thoughts that come with doves’ footsteps”: an unfinished conversation between George Steiner and Walter Benjamin - Soeiro, Ricardo Gil Costa (2025)
In “Thoughts That Come With Doves’s Footsteps”, an unfinished conversation between Walter Benjamin (1892-1940) and George Steiner (1929-2020) is tentatively rehearsed. In no way aiming at exhausting the complex connections that can be established between these two great thinkers of the 20th century, the present article only seeks to identify common cartographies, suggesting the crossing of trodden paths while testing elective affinities. Our main goal is to explore Steiner’s thought and to highlight the way in which Walter Benjamin’s footprints are insinuated in it: Steiner painting the portrait of Benjamin and Benjamin looking into the labyrinth of hope, pretending not to see the approaching angel with its little steps of a dove (Nietzsche).